Operation and control of a 1-Φ induction machine fed from a typical transformer-less photovoltaic (PV) cells - Suha Sabah Shyaa; Nihad Abdulkudhur Jasim; Yihia Hussein Takheal; Donya Nuhad Mahdy (Institute of Advanced Engineering and Science, 2023)
The work given in this paper illustrates how an adjustable speed 1-Φ induction machine's auxiliary winding is driven. Trina Solar's TSM-250PA05.08 array type model, which is made up of 1 series and 8 parallel-connected photovoltaic (PV) modules, feeds a single induction machine. PV system with perturb and observe (P&O) technique for maximum power point tracking (MPPT) tracking. The induction motor has been controlled using the field-oriented control (FOC) controlling approach. The outcomes of the 1-induction motor simulation were closely related to the parameters of insolation change. The outcomes are taken into account for the system's reaction FOC, which had been demonstrated in electromagnetic torque Te, main and auxiliary winding currents, and motor rotor speed.